Socio-economic impact of photovoltaic park: The Giurgiu County rural area, Romania - Mocanu, Irena; Mitrică, Bianca; Persu, Mihaela (Acta geographica Slovenica, 2019)
The paper aims to analyse the socio-economic territorial impact of photovoltaic parks in the rural area of Giurgiu County. The analysis valorises two types of data: the statistical information on the local socio-economic features provided by the National Institute of Statistics and the Giurgiu County Statistics Office, and the specific information about the photovoltaic parks revealed by the interviews applied to the local authorities during field investigation. The case-studies discussed in this paper reflect the socio-economic effects of building and operating the six photovoltaic parks as in the three rural local administrative units – LAU2: Izvoarele, Stăneşti and Malu. This study emphasizes four types of the socio-economic effects of investment in a photovoltaic project on: local rural economy, land use changes, local investments, budget and local labour market.